2015
DOI: 10.1177/1541931215591218
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Detection for Abrupt Onset Stimuli Presented via Head-Worn Display

Abstract: Head-worn displays have the potential to assist professionals in a wide variety of contexts by providing heads-up and hands-off information in real-time. For instance, nurses may be able to use head-worn displays to maintain peripheral awareness of the well-being of multiple patients while away from the nurses’ station and the patients’ beds. However, little is known about the advantages and disadvantages of head-worn displays in such contexts. In fact, many studies have shown that head-worn displays can lead … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…The patient-focused studies aimed to help individuals with motor impairments (8/21, 38%) [ 6 - 13 ], visual impairments (5/21, 24%) [ 14 - 18 ], developmental and psychiatric disorders (2/21, 9%) [ 19 , 20 ], weight management concerns (3/21, 14%) [ 21 - 23 ], allergies (1/21, 5%) [ 26 ], or other health concerns leading them to track specific physiological metrics (2/21, 10%) [ 24 , 25 ]. The clinician-focused studies analyzed Google Glass use in student training (9/30, 30%) [ 35 , 37 , 38 , 40 , 41 , 46 , 48 , 49 , 52 ], disaster relief (4/30, 13%) [ 27 - 30 ], diagnostics (2/30, 7%) [ 32 , 50 ], nursing (1/30, 3%) [ 33 ], autopsy and postmortem examination (1/30, 3%) [ 53 ], wound care (1/30, 3%) [ 54 ], behavioral sciences (1/30, 3%) [ 31 ], and various medical specialties, including cardiology (3/30, 10%) [ 43 - 45 ], radiology (3/30, 10%) [ 39 , 42 , 47 ], neurology (1/30, 3%) [ 34 ], anesthesiology (1/30, 3%) [ 36 ], pulmonology (1/30, 3%) [ 51 ], toxicology (1/30, 3%) [ 55 ], and dermatology (1/30, 3%) [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The patient-focused studies aimed to help individuals with motor impairments (8/21, 38%) [ 6 - 13 ], visual impairments (5/21, 24%) [ 14 - 18 ], developmental and psychiatric disorders (2/21, 9%) [ 19 , 20 ], weight management concerns (3/21, 14%) [ 21 - 23 ], allergies (1/21, 5%) [ 26 ], or other health concerns leading them to track specific physiological metrics (2/21, 10%) [ 24 , 25 ]. The clinician-focused studies analyzed Google Glass use in student training (9/30, 30%) [ 35 , 37 , 38 , 40 , 41 , 46 , 48 , 49 , 52 ], disaster relief (4/30, 13%) [ 27 - 30 ], diagnostics (2/30, 7%) [ 32 , 50 ], nursing (1/30, 3%) [ 33 ], autopsy and postmortem examination (1/30, 3%) [ 53 ], wound care (1/30, 3%) [ 54 ], behavioral sciences (1/30, 3%) [ 31 ], and various medical specialties, including cardiology (3/30, 10%) [ 43 - 45 ], radiology (3/30, 10%) [ 39 , 42 , 47 ], neurology (1/30, 3%) [ 34 ], anesthesiology (1/30, 3%) [ 36 ], pulmonology (1/30, 3%) [ 51 ], toxicology (1/30, 3%) [ 55 ], and dermatology (1/30, 3%) [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…In total, 40 studies were conducted in the United States [ 6 - 9 , 13 - 18 , 20 - 24 , 27 , 29 , 31 , 32 , 35 , 37 - 41 , 43 - 52 , 54 - 57 ], three in Germany [ 25 , 26 , 53 ], two in United Kingdom [ 10 , 11 ], China [ 34 , 36 ], and one each in Australia [ 33 ], Switzerland [ 42 ], Mexico [ 19 ], Netherlands [ 12 ], Norway [ 30 ], and Italy [ 28 ]. Less than half of the included studies (19/51, 37%) were conducted in a laboratory setting [ 6 - 9 , 12 , 14 , 16 - 19 , 21 - 24 , 27 , 31 , 33 , 42 , 50 ], 13 (25%) in a hospital setting [ 32 , 34 , 36 , 38 , 39 , 43 , 44 , 46 , 51 , 53 - 56 ], seven (14%) in a classroom or clinical student training setting [ 35 , 37 , 40 , 41 , 47 , 48 , 52 ], three in patient residences (6%) [ 13 , 15 ,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, previous research has shown that visual stimulus changes are harder to detect in the peripheral field of vision (Wolfe, O'Neill, & Bennett, 1998). Pascale et al (2015) showed that this effect is even stronger on a HMD compared to a conventional screen.…”
mentioning
confidence: 98%